2013
DOI: 10.1890/es13-00123.1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative biological assumptions strongly influence models of climate change effects on mountain gorillas

Abstract: Abstract. Endangered species conservation planning needs to consider the effects of future climate change. Species distribution models are commonly used to predict future shifts in habitat suitability. We evaluated the effects of climate change on the highly endangered mountain gorilla (Gorilla beringei beringei ) using a variety of modeling approaches, and assessing model outputs from the perspective of three spatial habitat management strategies: status quo, expansion and relocation. We show that alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Prior studies have found that GCMs induce as much variation in model results as RCPs (Wright et al 2014), but without following a predictable outcome. As others have previously found (McKenney et al 2011, Tuanmu 2012, Thorne et al 2013, Wright et al 2014, Goberville et al 2015, the choice of GCM had over a 10-fold impact on predicted range loss. Variation between predictions using different GCMs was more pronounced when employing the mechanistic model, which is likely explained by the finer temporal scale of environmental data necessary for the mechanistic model.…”
Section: Environmental Datamentioning
confidence: 57%
“…Prior studies have found that GCMs induce as much variation in model results as RCPs (Wright et al 2014), but without following a predictable outcome. As others have previously found (McKenney et al 2011, Tuanmu 2012, Thorne et al 2013, Wright et al 2014, Goberville et al 2015, the choice of GCM had over a 10-fold impact on predicted range loss. Variation between predictions using different GCMs was more pronounced when employing the mechanistic model, which is likely explained by the finer temporal scale of environmental data necessary for the mechanistic model.…”
Section: Environmental Datamentioning
confidence: 57%
“…3). This is obviously not the case, which suggests these species were possibly retracted in microrefugia (55, 56) that were not captured by the 10-km spatial resolution of the climate data we used, or that the SDMs for these species were overfitted, which is something to which SDMs for species with a small range size are prone (57). Given the evidence for forested conditions on lowland Sumatra and a lower percentage of wrongly predicted extinct species by MIROC-ESM, we consider our hindcasts with MIROC-ESM the more informative of the two.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our findings on the relationship between ecological factors and stress response suggest that Virunga mountain gorillas may have a harder time coping with warmer temperatures and more extreme rainfall. Thus, mountain gorillas might be more sensitive to warming trends than previous research has suggested (Thorne et al, ), since their small habitat restricts their ability to seek out colder temperatures (Loarie et al, ; La Sorte & Jetz, ). Climate models predict a temperature increase of 3.6°C, prolonged dry seasons, and a potential upward shift of flora communities of approximately 600 to 700 m in the region by 2090, relative to 1990 (McGahey et al, ; Warner et al, ).…”
Section: Discussionmentioning
confidence: 97%